Bromination of Cycloparaphenylenes: Strain‐Induced Site‐Selective Bis‐Addition and Its Application for Late‐Stage Functionalization. (19th July 2017) - Kayahara, Eiichi; Qu, Rui; Yamago, Shigeru
Abstract: Bromination of [ n ]cycloparaphenylenes (CPPs) is herein reported. Small [ n ]CPPs ( n <8) underwent a bis‐bromine addition reaction with high site selectively to produce tetrabromo adducts in moderate to excellent yields. Theoretical calculations revealed that thermodynamic stability dictates both the reactivity and site selectivity of the reaction. The addition product was further converted into the octabromo product by a FeBr3 ‐catalyzed site‐selective bromination reaction. The tetra‐ and octabromine adducts were then transformed into mono‐ to tetrabromo CPPs, which were further converted into several CPP derivatives. Therefore, bromination and subsequent transformations provide a path for late‐stage functionalization of CPPs.